Research on robot path planning based on fused Dijkstra and TEB algorithms - Li, Baogang; Ni, Kun; Zhou, Fa; Li, Yuhuan; Huang, Wanyou; Jiang, Hanjun; Liu, Fuhao (Journal of mechanical science and technology, 2025)
In the field of intelligent robots, various algorithms can be used to enable robots to achieve obstacle avoidance and autonomous navigation. However, when a wheeled mobile robot encounters obstacles and tries to bypass them during work, work efficiency and economy are usually affected due to the large turning radius. How to improve work efficiency and economy while ensuring safety has important research value. To address the above issues and improve work efficiency of intelligent robots working in structured environments, this paper proposes an improved timed elastic band (TEB) algorithm combined with Dijkstra algorithm for controlling wheeled mobile robots to complete the process of autonomous navigation and path planning, thereby achieving a better balance between safety and efficiency. The experimental results show that in the same path between the start and end points, the designed algorithm and method reduced the turning radius by 16.7 %, resulting in 4.1 % reduction in the overall operation time. The proposed fusion algorithm achieves higher efficiency and smoother paths, enabling the wheeled mobile robot to generate a better path trajectory.